Examining features and critical success factors of shared services in higher learning institutions - Jais J.; Naidu P. (American Institute of Physics Inc., 2023)
Endeavours to enhance the efficiency and effectiveness of organisations have been a persistent objective for business and government. Within this perspective, shared services have been introduced and promoted as an alternative to provide best solution. The aim of shared services is to centrally provide specific services in an organisation whereas those services had formerly been administered in more than one of organisation's parts. Notwithstanding its growing popularity and widespread application, there is a limited sign of shared services in higher institutions, suggesting a scarcity of empirical study in this issue. Thus, this paper aims to explore the key success factors in the implementation of shared services in the higher learning institutions via archival research method. The findings consolidate the archived information on shared services in nine higher education institutions in U.S, highlighting common critical features for the successful implementation of shared services. 2019 Author(s).